Дослідження протизапальної та анальгетичної активності похідних 7-n-хлорбензил-8-заміщених теофіліну - Григор’єва, Л. В.; Самура, Б. А.; Самура, Ірина Борисівна; Романенко, Микола Іванович; Grigorieva, L. V.; Samura, B. A.; Samura, I. B.; Romanenko, N. I. (My University, 2015)
Виконано експериментальне дослідження залежності протизапальної та анальгетичної активності від хімічної структури у ряді 7-n-хлорбензил-8-заміщених теофіліну. Найбільший протизапальний і анальгетичний ефекти проявила сполука № 5 - 7-n-хлорбензил-8-n-гідроксіфенілетиліденгідразинотеофіл іну, яка в дозі 14,2 мг/кг пригнічує розвиток каррагенінового набряку лапки у щурів на 46,8 % і виявляє знеболюючу дію в межах 45,8 %. Похідні 7- n -хлорбензіл-8-заміщених теофіліну є перспективною групою органічних речовин для подальшого проведення цілеспрямованого синтезу і дослідження фармакологічної активності з метою створення на їх основі субстанцій для приготування нових лікарських препаратів. The presented results indicate that the most pronounced effect was antie x udative compound number 5 − 7-p-chlorobenzyl-8-p-hydroxyphenylethylidenhydrazinotheophylline, is a dose of 14.2 mg/kg 4 hours after administration caused a reduction in the e x perimental rat paw edema by 46.8 %. Moving in the 8th position of the molecule 7-p-chlorobenzyl-8-p-hydroxyphenylethylidenhydrazinotheophylline (comp. 5) hydroxyphenylethylidenhydrazine p-fragment of o-hydroxyphenylethylidenhydrazine (comp. 6) reduced the anti-e x udative activity. Because replacement 8th position p-chlorobenzylidenhydrazine (comp. 5) on the o-radical hydroxybenzylidenhydrazine (comp. 1), (à-methyl)-p-chlorobenzylidenhydrazine (comp. 2) substituents inflammatory activity was 37.9 % and 32.8 % respectively. Antie x udative less pronounced effect is the substance contained in the 8th position of the molecule p-methoxybenzylidenhydrazine (comp. 3), p-nitrophenylethylidenhydrazine (comp. 4) and p-chlorobenzylidenhydrazine (comp. 8) substituents which inhibits the development of e x perimental carrageenan paw edema in rats on average 28.1 %, 25.1 % and 21.7 % respectively. Compounds 7 and 9 showed a tendency to inhibition of paw edema in rats of between 8. 9 % and 17.9 % respectively. Antie x udative active comparator diclofenac in a dose of 8 mg/kg was 45. 5 % (p < 0.05). Thus, among the studied 7-p-chlorobenzyl-8-substituted theophylline appeared most active comm. 5, antie x udative activity of which can be compared with the comparison drug diclofenac. The study of the analgesic activity of derivatives of 7-p-chlorobenzyl-8-substituted theophylline acetic conducted writhing model. Analysis of the results showed that 7-p-chlorobenzyl-8-substituted theophylline (comp. 1-9) rats reduce manifestations refle x reaction to a chemical stimulus in the range from 5.8 % to 45.8 %. The greatest analgesic activity manifested compound number 5 − 7-p-chlorobenzyl-8-p-hydroxyphenylethylidenhydrazinotheophylline, that at a dose of 14. 2 mg/kg, caused a decrease in the amount of acetic writhing on 45.8 % (p < 0.05). Substitution in the eighth position of the molecule 7-p-chlorobenzyl-8-substituted theophylline p-hydroxyphenylethylidenhydrazine (comp. 5) on the o-substituent hydroxyphenylethylidenhydrazine (comp. 6) and (à-methyl)-p-chlorobenzylidenhydrazine (comp. 2) leads radicals to reduce analgesic activity. Compounds 4 and 7 tendency to be found the refle x response to a chemical stimulus. The analgesic effect of these substances is in the range from 5.8 % to 14.4 %.
Study Anti-Inflammatory and Analgesic Activity of Derivatives of 7-P-Chlorobenzyl-8-Substituted Theophylline
Keywords: запалення; антиексудативна та анальгетична активність; похідні 7-п-хлорбензил-8-заміщених теофіліну; inflammation; analgesic and anti-e x udative activity; derivatives of 7-p-chlorobenzyl-8-substituted theophylline